2008
DOI: 10.1007/s10886-008-9507-2
|View full text |Cite
|
Sign up to set email alerts
|

Potato, Solanum Tuberosum, Defense Against Colorado Potato Beetle, Leptinotarsa Decemlineata (Say): Microarray Gene Expression Profiling of Potato by Colorado Potato Beetle Regurgitant Treatment of Wounded Leaves

Abstract: Colorado potato beetle (CPB) is a leading pest of solanaceous plants. Despite the economic importance of this pest, surprisingly few studies have been carried out to characterize its molecular interaction with the potato plant. In particular, little is known about the effect of CPB elicitors on gene expression associated with the plant's defense response. In order to discover putative CPB elicitor-responsive genes, the TIGR 11,421 EST Solanaceae microarray was used to identify genes that are differentially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 44 publications
1
57
0
3
Order By: Relevance
“…However, first indications emerging from recent work seem to contradict this view by demonstrating that insect herbivores might actively manipulate plant defence responses (Lawrence et al 2008;Pareja et al 2012;Schwartzberg et al 2011). Helicoverpa zea and Spodoptera exigua caterpillars' saliva contain glucose oxidases that reduce induced defences (Bede et al 2006;Musser et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, first indications emerging from recent work seem to contradict this view by demonstrating that insect herbivores might actively manipulate plant defence responses (Lawrence et al 2008;Pareja et al 2012;Schwartzberg et al 2011). Helicoverpa zea and Spodoptera exigua caterpillars' saliva contain glucose oxidases that reduce induced defences (Bede et al 2006;Musser et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Helicoverpa zea and Spodoptera exigua caterpillars' saliva contain glucose oxidases that reduce induced defences (Bede et al 2006;Musser et al 2002). Attacks by Leptinotarsa decemlineata beetles suppress transcription of genes encoding for proteinase inhibitors also involved in plant defence (Lawrence et al 2008). The silverleaf whitefly Bemisia tabaci biotype B prevents the activation of the jasmonic acid-regulated defences by Arabidopsis plants, which decreases plant defences and enhances nymphal performance (Walling 2008;Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, actual insect damage is not a prerequisite for reduced photosynthetic activity. Feeding by both chewing herbivores that remove leaf material (Reymond et al, 2004;Lawrence et al, 2008) and phloem-feeding insects that do not (Zhu-Salzman et al, 2004;Botha et al, 2006) resulted in lower levels of photosynthesis-related gene expression. Even plantperceived evidence of insect attack that does not lead to any actual damage (e.g.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Previous research has shown that application of OSs from Colorado potato beetle (CPB; Leptinotarsa decemlineata) larvae to mechanically wounded plants suppressed induced defenses in tomato and potato compared with wounded and water-treated plants (16)(17)(18). To investigate potential mechanisms of defense suppression by CPB larvae, we asked if microbes in OSs from CPBs manipulate induced defenses.…”
mentioning
confidence: 99%